How Chinese online critics oppose genetically modified foods: discourse analysis and food policy implications - Jinrong Lin; Xuekun Liu (Humanities & Social Sciences Communications)
Abstract This study examines public discourses of genetically modified foods (GMFs) on Chinese social media WeChat. Through a discourse-historical approach, it focuses on how critics of GMFs discursively construct and legitimate their views against GMFs and explores the ideologies underpinning their distrust. Findings show that opponents employ metaphors, ironies, moralization, and intertextuality to emotionally and morally appeal against GMFs, creating tensions with modern agricultural discourses. The paper reflects on researchers’ stance as critical discourse analysts in analyzing such a significant yet controversial topic and demonstrates the importance of keeping a neutral, yet critical position in revealing the nuances of debates about GMFs. Implications for food policy researchers to address arguments against GMFs are also discussed in this paper.